Netherlands : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in the Kingdom of the Netherlands during the 1990s. Following a slowdown in 1991-92, the Dutch economy experienced a mild recession in 1993 with GDP growth falling to about 1\2 percent. Output was sustained by external demand, which contributed nearly 1 percentage point to GDP growth, while domestic demand fell by 1\2 percent. Business investment decreased by 3 percent as a result of reduced profits and a low rate of capacity utilization, while the contribution to GDP of lower stockbuilding was - 1\2 percentage point.